Changes in VO2 Kinetics After Elevated Baseline Do Not Necessarily Reflect Alterations in Muscle Force Production in Both Sexes - do Nascimento Salvador, Paulo Cesar; Schäfer, Lisa; Grassi, Bruno; Guglielmo, Luiz Guilherme Antonacci; Denadai, Benedito Sérgio (Frontiers in Physiology, 2019)
A link between muscle fatigue, decreased efficiency and the slow component of oxygen uptake (VO2sc) has been suggested. However, a cause-effect relationship remains to be elucidated. Although alterations in VO2 kinetics after elevated baseline work rate have previously been reported, to date no study has observed the effect on muscle force production (MFP) behavior considering physiological differences between male and female subjects. This study investigated the effect of elevated baseline work rate on the VO2 kinetics and MFP in 10 male and 10 female healthy subjects. Subjects performed 4 transitions of very-heavy (VH) intensity cycling in a randomized order after unloaded (U-VH) or moderate (M-VH) exercise. Maximal isokinetic efforts (MIE) were performed before and after each condition at two different cadences (60 or 120 rpm). Whereas baseline VO2 and time constant (τ) were significantly higher in M-VH compared to U-VH, the fundamental amplitude and the VO2 slow component (VO2sc) were significantly lower in M-VH (p<0.05) in both sexes. Blood lactate concentration ([La]) and rate of perceived exertion (RPE) were not influenced by condition or sex (p>0.05). The MFP post-exercise was not significantly influenced by condition in both sexes and cadences (Δtorque for males: at 60 rpm in U-VH = 13 ± 10 Nm, in M-VH = 13 ± 9 Nm; at 120 rpm in U-VH = 22 ± 14 Nm, in M-VH = 21 ± 12 Nm; for females: at 120 rpm in U-VH = 10 ± 9 Nm, in M-VH = 12 ± 8 Nm; p>0.05), with the exception that female subjects presented smaller decreases in M-UH at 60 rpm compared to U-VH (11 ± 13 vs. 18 ± 14 Nm; respectively, p<0.05). There was no correlation between the decrease in torque production and VO2 kinetics parameters (p>0.05). The alterations in VO2 kinetics which have been suggested to be linked to changes in motor unit recruitment after elevated baseline work rate did not reflect alterations in muscle force production and fatigue in both sexes.